Development of Gayo Culture Based Learning Device with Realistic Approach - Zuhra Ruhmi; Cut Morina Zubainur; Yusrizal Yusrizal (SAINTIS Publishing, 2019)
Mathematical learning tools that integrate culture are needed to bring the learning of daily life together so that it can improve students' problem solving skills in learning as well as in life. This is a hope to be achieved in the implementation of education in the province of Aceh. But the learning device is not available yet. So it takes effort to help teachers develop the learning device. Gayo is one of the sub ethnic in Aceh Province. This study aims to determine the process and results of the development of learning devices based on Gayo culture with a valid, practical and effective realistic approach. The development model used in this research is the development of Plomp which consists of three stages: initial assessment, design / prototype, and assessment. The subjects of this research are VII grade students of SMP IT Azzahra as small test also big test to judge valid, practical and effective. The results of this study obtained the tools of learning mathematics based on Gayo culture has met the valid, practical and effective criteria.